HUBUNGAN KONSEP DIRI DAN PENYESUAIAN SOSIAL DENGAN SELF REGULATED LEARNING DI ERA PANDEMI COVID-19 - afrizawati; Resi Anggraini; Nurhayati (LP2M-Institut Agama Islam Abdullah Said Batam, 2021)
The COVID-19 pandemic has changed various aspects of life, including learning activities in the education system. This study aims to determine the relationship between self-concept and social adjustment with self-regulated learning in the era of the covid 19 pandemic. The subjects of the study were students of SMA Hidayatullah Batam. The number of subjects is 100 students with an age range of 17-19 years using the Cluster Random Sampling technique. The type of research in this study is correlational research, because this study aims to find out whether there is a relationship between one variable and another. Seeing whether or not there is a relationship between self-concept and self-regulated learning. Whether or not there is a relationship between social adjustment and self-regulated learning. Whether or not there is a relationship between self-concept and social adjustment together with self-regulated learning. The results of this study indicate that self-concept and social adjustment together have a relationship with self-regulated learning. Of the two independent variables, the social adjustment variable has no relationship with self-regulated learning. While the self-concept variable is a variable that has to do with self-regulated learning.